What is Missing in Entrepreneurship Education: A Case Study - Putu Ditta Agastya (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Entrepreneurship education is designed to create entrepreneurs. However, the percentage of self-employed Master of Business and Administration of Entrepreneurship (MBAE) graduates at a top-tier business school in Jakarta (TBS) is below ten percent. In the current curriculum, TBS requires their MBAE students to start and develop their own business under Business Initiation and Business Growth subjects. Nevertheless, that project-based learning program seems not effective to shape their students to be entrepreneurs. What is missing in entrepreneurship education? The low percentage of MBAE graduates to be entrepreneurs indicates a gap in entrepreneurship education between what is really needed by students as future entrepreneurs and what business school offers as an education provider. This study aims to: (1) investigate the factors that discourage MBAE students not to be self-employed after graduation, (2) have a holistic understanding of ideal entrepreneurship education from MBAE students' point of view, (3) identify the gap between MBAE students' and educator's perspectives about entrepreneurship programs. This study uses qualitative methods, conducting In-Depth Interviews (IDI) and Focus Group Discussions (FGD) among the current MBAE students, graduates, and educators. This study found that economic factors, financial risk, and personal development deter students from choosing entrepreneurship as a career. MBAE students expect an entrepreneurship education should accommodate a high intensity of knowledge relevance and application, real business experience, practitioner involvement, individual-level coaching, and business development support. This study also found that the business school failed to equip the students with relevant knowledge and its application to their own businesses. In order to fill the missing part in entrepreneurship education provided, TBS is suggested to implement (1) an entrepreneurship-focus internship program that concentrates on gaining firsthand experiences and knowledge acquired from entrepreneurs in a complex business environment and (2) a formal entrepreneurship training for facilitators to adapt with entrepreneurship dynamism. Keywords:   Entrepreneurship Education; Entrepreneurship Focus Internship; Phenomenography; Qualitative Method; Training For Entrepreneurship Facilitators